Victoria Garden (Jijamata Udyan) and Zoo, Entrance - Ghosh, Ayan (2023)
Victoria Garden was established as a botanical garden by the Agri Horticultural Society of Western India on Mount Estate, Byculla, on land donated by David Sassoon (1792-1864). In 1890, a zoo was added to the garden. In 1969, Victoria Garden was renamed Veermata Jijabai Bhonsle Udyan, though it is popularly known as Byculla Zoo or Mumbai Zoo.